Application of the "crossflow" microfiltration in the brewing industry. - S.G. BUGAN; D. ŠMOGROVIČOVÁ; Z. DÖMÉNY; J. STOPKA; Š SCHLOSSER (Kvasný průmysl, 2001)
The recovery of rest beer from used yeast by way of filtration on ceramic membranes is a component of the plant technology in the present modern brewing industry. The ceramic membranes made from highly clean alpha-aluminium oxide have proved their suitability. The membrane filtration can produce clear beer without yeast cells and bacteria. There is no danger of cell breakage so that the amount of fatty acids and the protease activity would not increase. The modular design of filtration operations provided flexibility for whatever size of brewery and its future capacity increase. Especially for breweries with enhanced capacity, the CMF equipment affords advantages due to its possibility of easy gradual capacity increase upto more than 100%(In Czech, English summary only)